Javanese Culture Maintenance throughTheTradition of Cutting Natural Dreadlock Hair of Dieng’s Children - Wiwiek Sundari (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2022)
Javanese culture is one of many great cultures in the world possessing seven universal elements of culture covering the complex systems of belief, social organization, knowledge, language, art, livelihood, and living tools. The languageitself has been used for ages and taught in some countries for quite some time as it has its own orthography, grammar, politeness levels, and dictionary. To preserve the culture, Javanese people supported by the government put various efforts such us teaching the culture, practicing the culture, and documenting parts of the culture that has no longer being used. This research appliedDundees’s folklore research method and Sania’s research on culture maintenance to show how Dieng people along with Banjarnegara’s local government preservethe culture through the tradition of cutting the natural dreadlock hair of particular Dieng’schildren. The result shows that this sacred ceremonyutilize the seven universal elements of Javanese cultureItmeans that tradition can be one of the ways to preserve culture so that it does not have to be threatened, replaced, or even extinct. Keywords: Javanese culture, culture maintenance, tradition, cutting children’s dreadlock hair, Dieng.